Talking Textiles, Making Value: Catalyzing Fashion, Dress, and Textiles Heritage in the Midlands. (2nd January 2020) - Hackney, Fiona; Baines, Emily; Bloodworth, Jo; McKenzie, Althea; Anderson, Claire; Wells, Ali; Howard, Catherine
Abstract: There are hundreds of small museums, archives, and collections in the English Midlands, United Kingdom (UK), many of which are the legacy of the region's rich industrial heritage. A surprising number of these include dress and textiles in various forms, from the costume collection of Charles Paget-Wade at Berrington Hall (Leominster) to intricately stitched smocks made by local needlewomen in Herefordshire, and the wealth of manufacturers' samples that comprise the silk ribbon trade archive at the Herbert Museum, Coventry. These are challenging times for many such organizations as they face cutbacks in staff and local authority funding. Yet they offer a unique and largely unexploited resource for staff, students, and researchers in art and design higher education (HE), not only for primary research but also as a catalyst for design innovation. The discussion here, which takes the format of group research practitioner interview, builds on a Knowledge Exchange event that was held December 2017 at the Fashion Lab, University of Wolverhampton (UoW). The event brought together a diverse group of fashion and textiles professionals to talk, exchange ideas, take part in object handling sessions, mind-map, and brain-storm how to catalyze connections between heritage collections and HE and build value. With seed funding from the Museum-University Partnership Initiative (see National Coordinating Center for Public Engagement—NCCPE 2019 ), the day built on a series of scoping visits to collections in the region undertaken by Professor Fiona Hackney and Dr Emily Baines. The group involved staff, students and museum professionals including those from UoW, De Montfort University, Hereford College of Arts, Nottingham Trent University, artist Ruth Singer who leads the Arts Council-funded Criminal Quilts project in association with Staffordshire Record Office (Singer 2019 ), and representatives from Herefordshire Museum Service, the Herbert Gallery (Coventry), Walsall Museums Service, the Lace Guild Stourbridge, and Ironbridge Gorge Museum Trust. The following conversation reflects themes that emerged in the project including: the need to embed archival work and primary research in fashion and textiles curricula at all levels, the development of hubs to connect university research with museum practice, the added value of artist-led projects, and the significance of place-based textiles heritage as a catalyst for new business and sustainable design practice.